Incidence of psychrotrophic lipolytic bacteria in cow's raw milk - R. Cempírková; M. Mikulová (Czech Journal of Animal Science, 2009)
The contamination of bulk samples of cow's raw milk (n = 491) by psychrotrophic lipolytic bacteria (PLiBC), total count of psychrotrophic bacteria (PBC) and mesophilic bacteria (TBC) was monitored for two years on eight dairy farms and the correlations among these groups of bacteria were analysed. An increase in TBC, PBC and PLiBC and in the values of free fatty acids (FFA) was tested experimentally in three milk samples in relation to time (analyses were done in 24-hour intervals until 96 hours) and storage temperature of milk samples (4; 6.5 and 10°C). Bacterial contamination of milk was determined by culture methods in accordance with IDF standards, the values of FFA were determined by an extraction-titration method. These mean values were determined in the set of samples (n = 491): PLiBC 659 CFU/ml, PBC 2 932 CFU/ml and TBC 18 932 CFU/ml. A high correlation was proved between values of PBC and PLiBC (r = 0.87; P < 0.001) while the correlation between TBC and PBC (r = 0.65; P < 0.001) and between PLiBC and TBC (r = 0.59; P < 0.001) was on a medium level. The proportional index pI for PLiBC/PBC was 0.20, for PLiBC/TBC 0.03 and for PBC/TBC 0.16. In seasonal dynamics a statistically significant difference (P < 0.001; P < 0.05) between the increased values of TBC in the summer season was proved compared to the winter and spring season. The differences in the seasonal variation of PBC and PLiBC values were not significant. Experimental investigation of an increase in the values of tested parameters showed that at temperatures of milk sample storage 4 and 6.5°C TBC did not exceed the permissible hygienic value (100 000 CFU/ml) even after 96 hours while at 10°C it amounted to 90 000 CFU/ml after 48 hours and the limit for TBC was exceeded several times after 96 hours. PBC, which is not inhibited by cold storage to such a large extent, did not exceed the hygienic limit value for PBC (50 000 CFU/ml) even after 96 hours when milk samples were stored at 4°C, but at 6.5°C after 72 hours and at 10°C already after 48 hours the values 6 and 20 times higher, respectively, than the hygienic limit were recorded. A similar trend was observed in PLiBC, which exceeded the hazardous limit (43 000 CFU/ml) at 6.5°C after 96 hours and at 10°C already after 48 hours whereas at 4°C the limit value was not exceeded even after 96 hours. The content of FFA also increased in relation to the storage time and temperature of milk samples but in comparison with the increase in the tested groups of microorganisms the increase in FFA showed a higher correlation with storage time compared to storage temperature. A medium correlation was calculated between PLiBC and/or PBC and FFA content (r = 0.52; r = 0.57; P < 0.001).